Moored ADCP and CTD data from Oslo Fjord - Arneborg, Lars (University of Gothenburg, 2019)
Velocity and CTD data från ADCPs and CT loggers moored at Ristsundet and Aspond in Oslo fjord between 20-23 June 2011.

Ristsundet: Position: N59.7215, E10.5702 Water depth: 82 m MicroCat SBE37 CTD loggers at 82, 45, 34, 25 and 14 m depth logging with 5 min intervals. RDI 300 kHz ADCP, upward looking, with two meter bins from 75 to 7 m depth, and 5 min ensemble intervals.

Aspond: Position: N59.7243, E10.5813 Water depth: 90 m MicroCat SBE37 CTD loggers at 89, 46, 36, 26 and 16 m depth logging with 5 min intervals. RDI 300 kHz ADCP, upward looking, with two meter bins from 84 to 6 m depth, and 5 min ensemble intervals.

Förtöjd ADCP- och CTD-data från Oslofjorden.

För mer information se den engelska katalogsidan: https://snd.gu.se/en/catalogue/study/ecds0116
Förtöjd ADCP- och CTD-data från Oslofjorden
Keywords: FJORDS; POTENTIAL DENSITY; SALINITY; HALOCLINE; CONDUCTIVITY; DENSITY; WATER MASSES; ADVECTION; OCEAN CURRENTS; WATER TEMPERATURE; POTENTIAL TEMPERATURE; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser